Examining of E-readiness in the Local Government toward Smart City A Study from Balangan Regency - Maisyarah, Maisyarah; Roziqin, Ali; Nugroho, Rossi Adi; Te, Alice Y.C (JURNAL ILMU SOSIAL, 2024)
Many local goverment in Indonesia faces challenges in implementing the Smart City program due to limited technology, infrastructure and human resources. This research aims to analyze inhibiting factors and provide suggestions for increasing government technology readiness (e-readiness) towards a Smart City. The locus of research is Balangan Regency, South Kalimantan. The research method involves interviews and observations of relevant Stakeholders. Data was collected from interviews with high-ranking government and community officials, as well as observations of infrastructure and technology services in Balangan Regency. The research results show that limited internet services, inadequate hardware and software infrastructure, limited budget, and lack of competent human resources are the main obstacles. These factors are influenced by geographic constraints, budget priorities, and lack of public awareness of the importance of technology. To overcome this, it is recommended that the government collaborate with the private sector, increase budget allocations, provide training to human resources, and carry out regular monitoring and evaluation of community readiness. In conclusion, efforts to increase government technology readiness towards a Smart city in Balangan Regency require collaboration between the government, private sector and society, as well as increased investment in infrastructure and human resources.